Editorial da Revista Porto Arte nº 39 ano 2018 - Corona, Marilice Villeroy; Carvalho, Ana Maria Albani de; Zielinsky, Monica; Silveira, Paulo Antonio; Barachini, Teresinha (PORTO ARTE: Revista de Artes Visuais, 2018)
.